The Effect of Antiretroviral Therapy (ART) on Obstetric Complications Risk in Pregnant Women with HIV: A Scoping Review - Ermiati, Ermiati; Syalsabilla, Melsya Meira; Lailatussya’diah, Rania Annisa; Anggrayni, Selfi Astriyan; Pinto, Feliciano (Journal of Nursing Care, 2025)
Antiretroviral therapy (ART) is a cornerstone in the management of HIV among pregnant women due to its ability to suppress viral load and prevent vertical transmission. However, its effectiveness on pregnancy outcomes remains a challenge because of the potential risk of obstetric complications. This scoping review aimed to map and summarize existing evidence on the association between ART use and obstetric complications among pregnant women living with HIV. The review was conducted using the Arksey and O’Malley framework and reported in accordance with the PRISMA-ScR guidelines. A comprehensive literature search was performed across Scopus, EBSCOhost, PubMed, and ScienceDirect to identify full-text English-language original studies published between 2020 and 2025. Study selection was guided by the Population–Intervention–Outcome framework, focusing on pregnant women with HIV receiving ART and associated obstetric complications. Out of 11,669 identified articles, ten met the inclusion criteria. The findings revealed that initiating ART before pregnancy reduced the risk of small-for-gestational-age (SGA) infants, while regimens based on non-nucleoside reverse transcriptase inhibitors (NNRTIs) and protease inhibitors (PIs) were associated with a higher risk of preterm birth compared to integrase strand transfer inhibitor (INSTI)–based regimens. Low birth weight (LBW) was more frequently observed when ART initiation occurred during the second trimester. Immunological, placental, metabolic, and psychosocial factors were also found to influence pregnancy outcomes. In conclusion, ART management should consider drug type, timing of initiation, and maternal condition to minimize obstetric risks. Future research is recommended to examine the longitudinal effects of ART regimens using a multidimensional approach to achieve more precise and context-specific therapeutic management.